Profile of Diagnosis and Procedures of Asthma Patients Hospitalized in Royal Prima Medan Hospital at 2018 - Vivian Leoditta Sitinjak; Nerseri Barus (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Asthma is a chronic inflammatory disease of the respiratory tract. The purpose of this study was to determine the description of the diagnosis and management of asthma inpatient at RSU Royal Prima Medan in 2018. This research was conducted using a case study design method, descriptive - retrospective, sample size 100 data of medical records of patients taken by purposive sampling, namely medical records the most complete data and analyzed with descriptive statistics. The results show that the youngest is 9 years old and the oldest is 85 years old, with 44 men and 56 women. The most common complaint is 74 shortness of breath and the most pharmacological management is beta2 agonist 100%. The conclusion was that the distribution of asthma was higher in women (56%) than in men (44%) and the most common complaint was shortness of breath (74%) and the most used combination treatment was Beta 2 + Corticosteroid + Ammonium Chloride Agonists. and Diphenhydramine + Paracetamol + Antibiotics (35%). Keywords: Asthma, Diagnosis and Management, Royal Prima Hospital Medan